On Understanding Religion: A Study of Abdul Karim Soroush’s Thoughts - Anshori, Muhammad - (KALAM, 2020)
This paper discussed the method of understanding religion according to the views of Abdul Karim Soroush. The main question of this paper is “What is the adequate method to understand religion according to Abdul Karim Soroush?”, and “How to do that?" It found out that Soroush has differentiated religion from human’s understanding of religion. In the context of the study of religious knowledge, the Qur’an must be distinguished from its exegesis, and the Hadith from its syarah (explanation). If they are not distinguished, said Soroush, we risk to put human’s understanding of religion at the same level of that of the Qur’an and the Hadith. They are obviously not the same. While the Qur’an is based on revelation, human’s interpretation of the Qur’an is a result of rational thinking. This means, religion is absolute and human’s understanding of the religion is relative. In understanding religious texts (the Qur’an and Hadith), Soroush also maintained the conceptual theory of contraction and expansion. This theory is regarded as one of Soroush’s original thoughts with regard to an endeavor of understanding religion: it is for this reason that his thoughts are significant to the contexts in which we are now living Islam.